An applied econometricians' view of empirical corporate governance studies - Axel Börsch-Supan; Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The economic analysis of corporate governance is en vogue. In addition to a host of theoretical papers, an increasing number of empirical studies analyze how ownership structure, capital structure, the structure of the board and the market for corporate control influence firm performance. This is not an easy task, and indeed, for reasons explained in this survey, empirical studies on corporate governance have more than the usual share of econometric problems. Aim of this paper is a critical survey of the recent empirical literature on corporate governance – in order to show which methodological lessons can be learned for future empirical research in the field of corporate governance, paying particular attention to German institutions and data availability.
Keywords: G30; 330; Corporate governance; Corporate Governance; Ökonometrie; Statistische Methode; Theorie; Deutschland